7 mbg '78 - 7e Biennale Internationale de la Gravure Krakow 1978. - 7e Biennale Internationale de la Gravure Krakow, 1978 (Krakow, : Ministerstwi Kultury i Sztuki, 1978)
Aanvik, Geir ; Ahlgren, Roy ; Aigasa, Masayoshi ; Alberti, Pedro ; Almeida, David Fernandes ; Alviani, Getulio ; Amano, Junji ; Amimoto, Tomoyo ; Ando, Nana ; De Andreis, Giovanbat-Tista ; Angovist, Olle ; Armleder, John Michael ; Asada, Hiroshi ; Assadour ; Atkinson, Julia ; Backen, Earle ; Bailly, Bernard J. ; Bassetti, Fiorenza ; Bastl, Friedrich ; Bastos, Hugo ; Batorska, Barbara ; Bayrle, Thomas ; Bcanev, Stoian ; Beer, Maria Luiza ; Belgeonne, Gabriel ; Beltran, Felix ; Benes, Jozsef ; Berdyszak, Jan ; Berges, Werner ; Berlinicke, Hartmut ; Berman, Marietta ; Bes, Peter ; Biedermann, Wolfgang E. ; De Blas, G. Juan Ignacio ; Blagowolin, Mikolaj ; Boumans, Bart ; Böckman, Bengt ; Brandi, Uwe ; Brunovsky, Albin ; Burchard, Hartwig ; Calderon, Juan ; McCall, Ann ; Caloenescu, Adina ; Capobianco, Domenick ; Rimer, Angel Cardillo ; Cave, Jim ; Ceretieli, Georgij ; Chaplin, Bob ; Chlanda, Marek ; Chodorowicz, Janusz ; Choung-Fux, Eva ; Chrest, George Thomas ; Ciobanu, Victor Vladimir ; McClafferty, Maria ; Clamar, Tullio ; Claus, Carlfriedrich ; Clement, George ; Coita, Nistor ; Colverson, Ian ; McCombs, Bruce ; Comstedt, Maud ; Contaratou, Sosso ; Contino, Jose ; Corneille ; Cortes, Antonio Diaz ; Cunliffe, Peter ; Cuprys, Jacek ; Damer, Jack ; DioHandi ; Dragomirescu, Radu ; Dragulj, Emir ; Drozdik, Orsolya ; Drum, Sydney M. ; Dubravec, Marcel ; Dugonjic, Tomislav ; Dumitrache, Adrian ; Dunikowski, Duniko Wincenty ; Dusik, Stano ; Dusek, Lubos ; Dwurnik, Edward ; Dykmans, Anne ; Ebihara, El ; Ecker, Robert ; Escher, Rolf ; Fajo, Jan ; Fasiecki, Andrzej ; Fiedler, Jochen ; Fijalkowski, Stanislaw ; Fister, Vinko ; Fleischer, Karin ; Fossick, Michael ; Frankl, Sofia ; Freiles, Antonio ; Fujiwara, Sakio ; Furnival, John ; Gagnon, Elizabeth Lilian ; etc.
biografie
boek